Novel missense variant in SPTBN2 possibly associated with spinocerebellar ataxia type 5 presenting as Parkinson´s disease - Gonzalez Rojas, Natalia; Enrique Ziliani, Javier (Open Science Journal, 2022)
Spinocerebellar ataxias are a heterogeneous group of neurodegenerative diseases. There are more than 40 subtypes described so far, being spinocerebellar ataxia type 5 (SCA5) a rare autosomal-dominant ataxia with pure cerebellum involvement. The gene responsible is the non-erythrocyte beta 2 spectrin gene (SPTBN2), encoding β-III spectrin, highly expressed in Purkinje cells. Onset is usually before 30 years, although it ranges from infancy to 70 years. The main clinical manifestations are limb and gait ataxia (> 90%); however, some patients also show trunk ataxia, sensory deficits, abnormal eye movements, dysarthria, and hyperactive deep tendon reflexes (25–90%).